M - Deighan, Samm (Leighton Buzzard : Auteur, 2019)
Fritz Lang's first sound feature, M (1931), is one of the earliest serial killer films in cinema history and laid the foundation for future horror movies and thrillers, particularly those with a disturbed killer as protagonist. Peter Lorre's child killer, Hans Beckert, is presented as monstrous, yet sympathetic, building on themes presented in the earlier German Expressionist horror films like The Cabinet of Dr. Caligari and The Hands of Orlac. Lang eerily foreshadowed the rising fascist horrors in German society, and transforms his cinematic Berlin into a place of urban terror and paranoia. Samm Deighan explores the way Lang uses horror and thriller tropes in M, particularly in terms of how it functions as a bridge between German Expressionism and Hollywood's growing fixation on sympathetic killers in the '40s. The book also examines how Lang made use of developments within in forensic science and the criminal justice system to portray a somewhat realistic serial killer on screen for the first time, at once capturing how society in the '30s and '40s viewed such individuals and their crimes and shaping how they would be portrayed on screen in the horror films to come.
Introduction: Fire, Voices and Torment; 1: A Murderer Among Us; 2: In the Hall of the Mountain King; 3: The Vampire of Düsseldorf and the Butcher of Hanover; 4: While the City Sleeps; 5: The Pleasure to End All Pleasures; Bibliography.
Includes bibliographical references.
Online resource; title from PDF title page (EBSCO, viewed October 2, 2019).
JSTOR
Keywords: M (Motion picture); Lang, Fritz, -- 1890-1976 -- Criticism and interpretation; Lang, Fritz, -- 1890-1976; M (Motion picture); PERFORMING ARTS -- Film -- History & Criticism; Criticism, interpretation, etc